Can Creative Accounting be Equated with Creativity and Called Positive? - Bachtijeva, Diana (Buhalterinės apskaitos teorija ir praktika, 2021)
The advent of creative accounting in the middle of the 20th century sparked great interest among researchers and practitioners. In the work of both foreign and Lithuanian scientists, this phenomenon is widely researched and defined as the ability to use the flexibility of legal acts in order to reflect subjective information in financial statements. However, in contrast to foreign literature, linguistic interpretations of the term "creative accounting" appeared in Lithuanian literature, which gave this phenomenon a positive meaning, associated with creativity and identified as positive creative accounting. The article examines the concept of creativity, its relationship with accounting, assesses the compatibility of creativity with creative accounting. Based on the analysis of the literature, it is proposed to refuse to divide creative accounting into positive and manipulative, as such a division not only contradicts the concept of creativity, but also undermines the essence of accounting and its multiplicity.
Keywords: creative accounting; positive creative accounting; creativity